Visionary Leadership and Its Impact on the Quality of Education in Islamic Educational Institutions - Hidayah, Nurul (LETIGES, 2025)
Visionary leadership plays a crucial role in the advancement of educa-tional institutions, particularly in shaping institutional direction and im-proving educational quality. This study examines the role of visionary leadership in Islamic educational institutions, focusing on its influence on institutional management and educational outcomes. Using a qualitative multi-case study approach, the research was conducted at Madrasah Ali-yah Negeri 3 Malang and Leading Madrasah Aliyah PP Amanatul Ummah Surabaya. The findings reveal that visionary leadership in both institu-tions is actively implemented and characterized by religious integrity and strategic institutional development. The leadership functions encompass setting direction, designing strategies, acting as a change agent, motivat-ing stakeholders, solving institutional challenges, and establishing educa-tional standards. To achieve these objectives, visionary leadership em-ploys various strategic approaches, including formulating a shared vi-sion, implementing structured action plans, empowering stakeholders, fos-tering collaboration, and maintaining high educational standards. The ef-fectiveness of visionary leadership is evident in its ability to enhance edu-cational input, processes, and outcomes, leading to improved academic performance and institutional achievements. These findings provide valu-able insights for educators and policymakers in strengthening leadership strategies that integrate religious values and modern educational princi-ples to ensure sustainable academic excellence in Islamic institutions.